Preparation of nano-biochar from conventional biorefineries for high-value applications. (April 2022) - Song, Bing; Cao, Xuewen; Gao, Wenran; Aziz, Shazed; Gao, Shuai; Lam, Chun-Ho; Lin, Richen
Abstract: Nano-biochar presents superior physicochemical properties over bulk biochar such as highly stable and unique nanostructure, high catalytic activity and large specific surface area. A comprehensive understanding of the current nano-biochar research is required while progressing to real-world implementations, including preparation, characteristic properties and targeted applications. This paper provides a state-of-the-art review on nano-biochar research for (1) definition and production methodologies, (2) compositions and properties, (3) high-value applications and performances, (4) environmental concerns, and (5) implications to conventional biorefineries and perspectives. Following a sequence of biochar preparation, size reduction and screening, nano-biochar can be obtained for high-value applications such as a high-performance adsorbent, a carrier of biocatalysts, electrodes in electrochemistry and additives. Compared with bulk biochar, nano-biochar performs better in general uses such as wastewater treatment and soil amendment and promises high-value applications in emerging areas such as electrochemistry and biocatalysis. This review highlights that the preparation of nano-biochar from conventional bioenergy and biorefinery technologies such as thermochemical liquefaction and gasification is promising to generate adding values, contributing to enhanced techno-economic feasibility. Integrating nano-biochar preparation and application with conventional biofuel production is thus highly recommended as a future research endeavour. Graphical abstract: Image 1 Highlights: Nano-biochar is obtained from biochar via size reduction and particle screening. Nano-biochar has distinctive physiochemical properties compared with bulk biochar. Nano-biochar promises high-value applications in electrocatalysis and biocatalysis. Introducing nano-biochar production to biorefineries may boost the overall economy.